Commodity Markets Outlook, April 2018 - World Bank Group (World Bank, Washington, DC, 2018)
Commodity prices strengthened in the first quarter of 2018. Broad-based price increases were supported by both demand and supply factors. Accelerating global growth lifted demand for commodities, while a number of commodities faced supply constraints. For oil and precious metals, concerns about mounting geopolitical risk also supported prices. Crude oil prices are expected to average $65 per barrel (bbl) in 2018 (up from $53/bbl in 2017) and remain at $65/bbl in 2019—an upward revision from the October 2017 forecast. Metals prices are expected to increase 9 percent in 2018 and, following three years of relative stability, agricultural prices are expected to gain 2 percent in 2018. Looking ahead, policy actions currently under discussion, such as additional tariffs, production cuts, and sanctions, present risks to the short-term outlook. This edition also analyzes the policies of oil exporting economies in response to the 2014 oil price collapse. It concludes that oil exporters with flexible currency regimes, larger fiscal buffers, and more diversified economies fared better than others. The experience of the past four years is a reminder of the urgent need for greater economic diversification and stronger monetary and fiscal policy frameworks in oil exporters.